It's only discrimination when they do it to us: When White men use ingroup‐serving double standards in definitional boundaries of discrimination. (10th July 2022) - West, Keon; Greenland, Katy; van Laar, Colette; Barnoth, Ditte
Abstract: There is a widespread agreement that discrimination is bad, but disagreement about how discrimination is defined and identified. Discrimination is sometimes defined narrowly (including only a restricted range of behaviours), and sometimes broadly (encompassing a wide range of behaviours). Three experiments (the latter two preregistered) found that White men define sexist discrimination (Study 1, N  = 88) and racist discrimination (Study 2, N  = 130; Study 3, N  = 128) more narrowly when it was committed by their group against others and more broadly when it was directed against their group by others. Collective narcissism moderated (i.e. exacerbated) this effect in all three studies. However, when social dominance orientation (SDO) was considered simultaneously, it emerged as the more reliable moderator (Study 3). These results highlight that definitions of discrimination are not static but employed flexibly depending on context and hierarchy‐supporting motivations.